Meta-analysis of probiotics metabolites in gastrointestinal tract and metabolic health - Ma, Xiangning; Zhang, Hongjun (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe gastrointestinal (GI) tract acts as an essential interface between the host and the microbiota, with microbial metabolites exerting a significant role in regulating host physiology.MethodsIntegrative network-based methodology that combines metabolite-protein interactions with tissue-specific transcriptomics to uncover host targets of probiotic-derived metabolites and determine their potential biological significance. Utilizing curated interaction data, it is about to construct metabolite-host protein network and prioritised genes using centrality metrics. Gene expression analysis across human tissues indicated that some high-degree genes, including SLC27A4, LCN12, and APOD, are abundant in GI areas including small intestine, colon, and duodenum, indicating a potential role in local host-microbe interactions. Further metabolite-specific expression analysis revealed separate but overlapping expression landscapes. 10-hydroxy-cis-12-octadecenoic acid has been associated to increased production of sialyltransferases and neuraminidase in metabolically and immunologically active tissues.Results and discussionGlycodeoxycholic acid was associated with high levels of lipocalins and fatty acid transporters in enterohepatic tissues, indicating functions in bile acid metabolism and lipid transport. Meanwhile, N-(1-carbamoyl-2-phenyl-ethyl) butyramide was linked to detoxifying enzymes that are highly expressed in the liver, kidney, and gastrointestinal tissues. Collectively, these data reveal a tissue-specific molecular architecture that governs host responses to microbial metabolites, notably in the GI tract. Our findings shed light on how microbial compounds interact with host pathways at both the local and systemic levels, paving the way for new microbiome-targeted treatments and precision feeding initiatives.